The Market Structure of Commercial Banking in the United States - Alhadeff, David A. (Quarterly Journal of Economics, 1951)
I. Introduction, 62. — II. Some salient features of a banking market, 63. — III. Prices, profits, costs, 69. — IV. Banking market structure in small market towns and large cities, 73. — V. Impact of horizontal combination on banking structures, 79. — VI. Concluding observations, 83.